Congenital hypothyroidism – what's new?. Issue 7 (July 2015) - Lane, Laura C.; Cheetham, Tim
Abstract: Congenital hypothyroidism (CHT) represents an anatomical, biochemical and clinical spectrum with associated implications in terms of management and outcome. At one end of the spectrum of primary thyroid dysfunction is the child with thyroid agenesis and no significant endogenous thyroid function. This baby will require full thyroxine replacement. At the other end of the spectrum is the baby with a subtle increase in thyroid-stimulating hormone (TSH) levels, a normally sited thyroid gland and significant associated endogenous thyroid hormone generation. This baby will require a smaller dose of thyroxine supplementation to normalise TSH concentrations. The TSH 'threshold' that warrants intervention is unknown, although local thyroid hormone 'normal ranges' may be derived from adults and hence may not be representative of thyroid hormone levels in healthy neonates. The outlook for treated babies with CHT is excellent but there may still be subtle, long-term consequences of relatively low thyroxine concentrations in utero despite prompt diagnosis and treatment.